Transparent triboelectric generators based on glass and polydimethylsiloxane. (December 2016) - Chen, Jinkai; Guo, Hongwei; Ding, Peng; Pan, Ruizheng; Wang, Wenbo; Xuan, Weipeng; Wang, Xiaozhi; Jin, Hao; Dong, Shurong; Luo, Jikui
Abstract: Glasses are widely used in modern society, mostly for achieving brightness for buildings, transportations etc. Here a transparent triboelectric generator (TEG) based on commercially available glasses and polydimethylsiloxane (PDMS) plates is proposed and fabricated to harvest mechanical energy. Using flat glass and PDMS plates, an open voltage, short-circuit current and power up to 850 V, 20.6 μA and 3.13 mW are achieved for devices with 5 cm×5 cm dimension, whereas the transparency of glass and PDMS structures exceeds 81% and 89%, respectively. The TEGs show excellent mechanical stability and reliability upon cyclical contact for 10, 000 times. The voltage and power outputs of the glass based TEGs improve with increasing contact force, frequency and distance, and with decreasing glass thickness and humidity level. Our results demonstrate the feasibility to utilize abundant glass windows to fabricate transparent TEGs for energy harvesting, which could make a great contribution to the sustainable development. Graphical abstract: Glass TEG shows good transparency, electric performance and the feasibility to turn the abundant glass windows into energy harvesting applications. Highlights: Transparent TEGs based on commercial glasses have been developed. The outputs of the TEGs increase with contact force, frequency and distance, and with decreasing glass thickness. An improved model has been proposed for the TEG with excellent agreement with experiments. The TEGs have excellent stability without deterioration after tens of thousands contacts.